Adaptability and resilience to COVID-19: 8 cases of rural tourism in indigenous communities in central Mexico. - González Domínguez, Irais; Humberto Thomé-Ortiz; García Rodea, Luis Felipe (Anais Brasileiros de Estudos Turísticos, 2022)
The rural space has undergone important processes of social adaptability since the incorporation of tourist activities as a complement to the economic income of rural families, associated with the “New Rurality” concept. In the case of rural tourism in central Mexico, the incipient development of a complementary activity can be observed, whose positive impact on the communities was just beginning to gain strength in the face of a highly urbanized society, which demands the multiple benefits of rural spaces. However, the outbreak of the pandemic caused by COVID-19, led to the abrupt closure of non-essential activities and the loss of jobs and additional income generated by tourism. Faced with this disruptive scenario, multiple social actors, who had turned towards the logic of multifunctionality of the rural space, have been forced to deploy various adaptive strategies to adjust to the "new normal", the aim of this manuscript is the analysis of these adaptation processes. It is concluded that the complex and heterogeneous nature of rural societies is an important reservoir of survival strategies that will become increasingly important in the face of an uncertain future, associated with the eminent crisis of the Anthropocene.